Severe SARS-CoV-2 Infection in a Pediatric Patient Requiring Extracorporeal Membrane Oxygenation - Shannon M. Flood; Christina M. Osborne; Blake Martin; S. Christopher Derderian; Erin Stenson; Joseph A. Grubenhoff (Case Reports in Pediatrics)
The overwhelming majority of pediatric cases of SARS-CoV-2 infection are mild or asymptomatic with only a handful of pediatric deaths reported. We present a case of severe COVID-19 infection in a pediatric patient with signs of hyperinflammation and consumptive coagulopathy requiring intubation and extracorporeal membrane oxygenation (ECMO) and eventual death due to ECMO complications.